Therapeutic Management of the Hallux Rigidus. (5th September 2012) - Aggarwal, Anoop; Kumar, Suraj; Kumar, Ratnesh
Abstract : Background . Hallux rigidus is a chronic, disabling condition of foot characterized by reduced great toe extension. The manual therapy approaches are described theoretically however their practical published evidence has not been analyzed well. Objective . Aim of the present paper was to systematically review the literature available for therapeutic management of the hallux rigidus by identifying and evaluating the randomized controlled trials (RCTs) and non-RCTs. Methods . To view the hallux rigidus and its rehabilitation, a webbased published literature search of Pubmed, Ovid Medline, Science direct, Cochrane Database, PEDro database, CINAHL was conducted for last 35 years in August 2010 using 4 specific keywords "hallux rigidus, physical therapy, chiropractic, and manual therapy" typed in exactly same manner in the search column of the databases. Result . the review finds that there is acute need of the quality studies and RCTs for the manual therapy, chiropractic, or physiotherapeutic management of the hallux rigidus. Conclusion . Review conclude that conservative programs for hallux rigidus consists of comprehensive intervention program that includes great toe mobilization, toe flexor strengthening, sesamoid bones mobilization and long MTP joint. The clinician should put an emphasis on the mobilization program with proper follow up along with comparative studies for rehabilitation of hallux rigidus.